The Role of Fairness Ideals in Coordination Failure and Success - Andrzej Baranski; Ernesto Reuben; Arno Riedl (Institute of Labor Economics (IZA), 2025)
In a laboratory experiment, we study the role of fairness ideals as focal points in coordination problems in homogeneous and heterogeneous groups. We elicit the normatively preferred behavior about how a subsequent coordination game should be played. In homogeneous groups, people share a unique fairness ideal how to solve the coordination problem, whereas in heterogeneous groups, multiple conflicting fairness ideals prevail. In the coordination game, homogeneous groups are significantly more likely than their heterogeneous counterparts to sustain efficient coordination. The reason is that homogeneous groups coordinate on the unique fairness ideal, whereas heterogeneous groups disagree on the fairness ideal to be played. In both types of groups, equilibria consistent with fairness ideals are most stable. Hence, the difference in coordination success between homogeneous and heterogeneous groups occurs because of the normative disagreement in the latter types of group, making it much harder to reach an equilibrium at a fairness ideal.
Keywords: H41; C92; D63; 330; fairness ideals; focal points; coordination; cooperation; experiment